Elucidation of conditions allowing conversion of penicillin G and other penicillins to deacetoxycephalosporins by resting cells and extracts of Streptomyces clavuligerus NP1 - Cho, Hiroshi (National Academy of Sciences, 1998)
Using resting cells and extracts of Streptomyces clavuligerus NP1, we have been able to convert penicillin G (benzylpenicillin) to deacetoxycephalosporin G. Conversion was achieved by increasing by 45× the concentration of FeSO(4) (1.8 mM) and doubling the concentration of α-ketoglutarate (1.28 mM) as compared with standard conditions used for the normal cell-free conversion of penicillin N to deacetoxycephalosporin C. ATP, MgSO(4), KCl, and DTT, important in cell-free expansion of penicillin N, did not play a significant role in the ring expansion of penicillin G by resting cells or cell-free extracts. When these conditions were used with 14 other penicillins, ring expansion was achieved in all cases.